Feeling Anxious Amid the COVID-19 Pandemic: Factors Associated With Anxiety Symptoms Among Nurses in Hong Kong - Yeung, Nelson Chun-yiu; Wong, Eliza Lai-yi; Cheung, Annie Wai-ling; Yeoh, Eng-kiong; Wong, Samuel Yeung-shan (Frontiers in Psychology, 2021)
Background. The coronavirus (COVID-19) pandemic has increased the burden for the medical systems around the world. In Hong Kong, the pandemic not only affects the local populations, but also the healthcare workers. Healthcare workers, especially nurses, involving in COVID-19 treatments are highly susceptible to adverse psychological outcomes (e.g., anxiety symptoms). Studies have shown that socio-demographic characteristics, COVID-19-specific worries, and work settings-related variables are associated with healthcare workers’ well-being during the COVID-19 pandemic. However, relevant studies for nurses in Hong Kong are limited. This study examined the psychosocial correlates of anxiety symptoms among nurses in Hong Kong. Methods. Nurses (N=1510) working in hospitals and community settings were recruited through nursing associations in Hong Kong between August 8, 2020 and September 22, 2020. They were invited to complete a cross-sectional survey measuring their anxiety symptoms, sociodemographic characteristics, COVID-19-specific worries, and satisfaction with work and workplace pandemic-control guidelines. Results.17.2% of nurses reported moderate to severe levels of anxiety symptoms. Results from hierarchical regressions found that higher COVID-19-specific worries (contracting COVID-19, family members contracting COVID-19 due to their nursing work, insufficient protective equipment at workplace) (βs ranged from 0.07 to 0.20, ps<.01), higher perceived stigma of being a healthcare worker (β=0.18, p<.001), and lower work satisfaction (β=-0.21, p<.001) were associated with higher anxiety symptoms. Conclusion. A moderate proportion of nurses in Hong Kong did report levels of anxiety symptoms amid the COVID-19 pandemic. Futures studies could focus on the contributing factors of anxiety symptoms to design for effective strategies to promote nurses’ well-being during pandemic situations.